The use of rapid dengue diagnostic tests in a routine clinical setting in a dengue-endemic area of Colombia - Lyda Osorio; Marcela Uribe; Gloria Ines Ardila; Yaneth Orejuela; Margarita Velasco; Anilza Bonelo; Beatriz Parra (Memorias do Instituto Oswaldo Cruz, 2015)
There is insufficient evidence of the usefulness of dengue diagnostic tests under routine conditions. We sought to analyse how physicians are using dengue diagnostics to inform research and development. Subjects attending 14 health institutions in an endemic area of Colombia with either a clinical diagnosis of dengue or for whom a dengue test was ordered were included in the study. Patterns of test-use are described herein. Factors associated with the ordering of dengue diagnostic tests were identified using contingency tables, nonparametric tests and logistic regression. A total of 778 subjects were diagnosed with dengue by the treating physician, of whom 386 (49.5%) were tested for dengue. Another 491 dengue tests were ordered in subjects whose primary diagnosis was not dengue. Severe dengue classification [odds ratio (OR) 2.2; 95% confidence interval (CI) 1.1-4.5], emergency consultation (OR 1.9; 95% CI 1.4-2.5) and month of the year (OR 3.1; 95% CI 1.7-5.5) were independently associated with ordering of dengue tests. Dengue tests were used both to rule in and rule out diagnosis. The latter use is not justified by the sensitivity of current rapid dengue diagnostic tests. Ordering of dengue tests appear to depend on a combination of factors, including physician and institutional preferences, as well as other patient and epidemiological factors.